PTB's radiometric scales for UV and VUV source calibration based on synchrotron radiation. (25th April 2018) - Klein, Roman; Kroth, Simone; Paustian, Wolfgang; Richter, Mathias; Thornagel, Reiner
Abstract: The radiant intensity of synchrotron radiation can be accurately calculated with classical electrodynamics. This primary realization of the spectral radiant intensity has been used by PTB at several electron storage rings which have been optimized to be operated as primary source standards for the calibration of transfer sources in the spectral range of UV and VUV for almost 30 years. The transfer sources are compared to the primary source standard by means of suitable wavelength-dispersive transfer stations. The spectral range covered by deuterium lamps, which represent transfer sources that are easy to handle, is of particular relevance in practice. Here, we report on developments in the realization and preservation of the radiometric scales for spectral radiant intensity and spectral radiance in the wavelength region from 116 nm to 400 nm, based on a set of deuterium reference lamps, over the last few decades. An inside view and recommendations on the operation of the D2 lamps used for the realization of the radiometric scale are presented. The data has been recently compiled to illustrate the chronological behaviour at various wavelengths. Moreover, an overview of the internal and external validation measurements and intercomparisons is given.